2013
DOI: 10.1182/blood-2012-06-438937
|View full text |Cite
|
Sign up to set email alerts
|

SOX11 regulates PAX5 expression and blocks terminal B-cell differentiation in aggressive mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is one of the most aggressive lymphoid neoplasms whose pathogenesis is not fully understood. The neural transcription factor SOX11 is overexpressed in most MCL but is not detected in other mature B-cell lymphomas or normal lymphoid cells. The specific expression of SOX11 in MCL suggests that it may be an important element in the development of this tumor, but its potential function is not known. Here, we show that SOX11 promotes tumor growth in a MCL-xenotransplant mouse model. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
118
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 40 publications
5
118
3
3
Order By: Relevance
“…[14][15][16] SOX11 knockdown in mantle cell lymphoma cell lines resulted in PAX5 downregulation, increased expression of BLIMP1 and XBP1 and a switch in the gene expression signatures from a mature B-cell to an early plasmacytic differentiation profiling. 13 These findings suggested that SOX11 could contribute to mantle cell lymphoma lymphomagenesis by blocking the terminal B-cell differentiation program of the cells as a similar mechanism observed in the inactivating mutations of PRDM1/BLIMP1 in diffuse large B-cell lymphoma or the forced expression of PAX5 by the t (9;14)(p13;q32) in some B-cell lymphomas. [17][18][19] However, whether primary mantle cell lymphoma may modulate terminal B-cell differentiation features in relation to SOX11 expression is not well known.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…[14][15][16] SOX11 knockdown in mantle cell lymphoma cell lines resulted in PAX5 downregulation, increased expression of BLIMP1 and XBP1 and a switch in the gene expression signatures from a mature B-cell to an early plasmacytic differentiation profiling. 13 These findings suggested that SOX11 could contribute to mantle cell lymphoma lymphomagenesis by blocking the terminal B-cell differentiation program of the cells as a similar mechanism observed in the inactivating mutations of PRDM1/BLIMP1 in diffuse large B-cell lymphoma or the forced expression of PAX5 by the t (9;14)(p13;q32) in some B-cell lymphomas. [17][18][19] However, whether primary mantle cell lymphoma may modulate terminal B-cell differentiation features in relation to SOX11 expression is not well known.…”
mentioning
confidence: 83%
“…10,11 The oncogenic potential of SOX11 has been confirmed experimentally by SOX11-knockdown studies that have shown a significant reduction of tumor growth in vivo of xenografted SOX11-negative mantle cell lymphoma cell lines. 12,13 The oncogenic mechanisms of SOX11 in mantle cell lymphoma pathogenesis are not well understood. We have recently shown that PAX5 is one of the genes directly regulated by SOX11 in these tumor cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, a subset of patients follows an indolent clinical evolution with stable disease even in the absence of chemotherapy (6,7). This favorable behavior has been associated with IGHV-mutated (8,9) and lack of expression of SOX11 (10, 11), a transcription factor highly specific of MCL that contributes to the aggressive behavior of this tumor (12). However, the molecular mechanisms responsible for this clinical heterogeneity are not well understood.…”
mentioning
confidence: 99%
“…Неки тумори имају додатне алтерације у генима попут ТП53, што води агресивнијој прогресији болести 12,14,15 . Одсуство SOX11 или низак Ki-67 су у узајамном односу са неагресивном формом MCL; SOX11 производи туморски раст MCL ћелија и регулише транскрипцију 17 . Једна од најснажнијих директних мета SOH11 je PAX5, главни регулатор диференцијације B-ћелија.…”
Section: уводunclassified